Engaging with Bediuzzaman Said Nursi: a model of interfaith dialogue / By Ian S. Markham - Mohd. Dom, Adi Setia (Oxford University Press, 2011)
This book is the result of the author’s engagement with Nursi’s engagement with the challenges of state-imposed seculariztion in post-Ottoman Turkey. As a prominent Anglican theologian trying to come to grips with the secularization process in England, the United States and in the West in general, he believes that there is much that serious Christians can learn from the way Nursi, the foremost Muslim theologian of the Ottoman-Atatürk era, successfully renewed the faith of ordinary Turkish people in the face of Attatürk’s aggressive secularization of the country.